Assessing T-lymphocyte activation by non-conventional metabolomics - Ramalhete, Luís (2019)
The current methodologies to evaluate T-cell function are based on very laborious or/and expensive methods. Nevertheless, the assessment of the appropriate functioning of these cells is very important in the clinical context, namely as a diagnostic tool of T-cell alloreactivity in different hematological settings, solid organ transplantation and immunosuppressive therapy. In the present work, we evaluated the potential of Non-conventional Metabolomics (NM) based on FTIR spectroscopy, in the assessment of T lymphocyte function after mitogen activation by phytohemagglutinin (PHa).